Ummi Method in Early Children Learning The Qur`an - Gina Aulia; Fitra Fadilah; Imam Tabroni; Miftahul Fauzan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to find out how to apply the Ummi method in the Perum Citarum Bekasi area to early childhood. The research method used is qualitative because the data is of a value nature and requires data collection techniques through observation, interviews, and documentation about the implementation of the Ummi method and the effectiveness of the method. Data analysis is done using triangulation. The results of the study stated that early childhood really likes learning the Qur'an using this method. This method is applied by the teacher slowly, lovingly, not giving sanctions, and is guiding until one can read the Qur'an properly and correctly. Parents who have busy work cannot provide meaningful learning of the Qur'an. This type of parents tend to leave the process of learning the Qur'an to other people such as ustadz and ustadzah. Meanwhile, parents who do not have a profession outside the home, especially mothers, are divided into two. First, for those who know the importance of learning the Qur'an using the Ummi method, they carry it out with full responsibility while the other type who do not understand learning the Qur'an using the Ummi method tend to be indifferent to their children.